The evolution of the Avacongress - Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2009)
In the early 1990’s MBA educations started independently in Warsaw, Prague, and Debrecen. In the middle 1990’s a small network was estblished with the mentioned institutions, as well as supporters from different universities like Wageningen, Aberdeen, Cork, later Fayetteville fromArcansas (USA). In the beginning of the 21st century the network became bigger. That time did Kiev join the Network, and started negotiations with Moscow Paralell to extended network leading by Warsaw University we applied for a EU Leonardo grant. The proposal was to develop the teaching and learning materials in the programme to a common approved standard. In order to improve the quality of teaching a set of commonly approved, standardized teaching materials had been eveleoped: Handbooks fo rmodules taught within 7 courses of the MBA programs: Public Policy, Economics, Management, Marketing, Finance, Operational Methods and International Agribusiness. Handbooks and case studies had been put on Warsaw University’s website and are now accessible for teachers and students from all academic institutions participating in the project. Materials had been developed by teams of experts in specific fields from different Universities.The whole set of materials was prepared in English. Another product of the project is the quality assurance standards applied by all MBA programs and an accreditation procedurefor the International Board. That time formulated the name AGRIMBA which is official name of the International Network on Agribusiness and Commerce.